Congenital myopathies in adults - a diagnosis not to overlook - Bárbara Alves Passos (2022)
Background: Congenital myopathies (CM) were traditionally classified according to the muscle histopathological features, but in recent years, molecular diagnosis has become increasingly important. CM may present a wide phenotype variability, and while adult-onset CM have been increasingly recognized, substantial diagnostic delays are still reported. Methods: We performed a retrospective observational cohort study to characterize the CM patients evaluated in our adult Neuromuscular outpatient clinic, including the subgroup of adult-diagnosed patients. Results: We identified 19 CM patients with compatible molecular and/or histological diagnoses, of which 14 were diagnosed in adulthood. Eleven adult-diagnosed patients had symptoms since childhood and 9 had a family history of myopathy. The median age of symptoms' onset was 4 years old and the median age at diagnosis was 37 years old. The most common causative gene was RYR1, followed by TTN and MYH7. Three patients had non-specific features on muscle biopsy, all diagnosed during adulthood. Conclusions: In our cohort, the majority of CM were diagnosed in adulthood, despite most having pediatric-onset symptoms and positive family history. The diagnostic delay may be associated with mild presentation, slow course, atypical muscle histology and lack of awareness of adult-onset CM. Studies with larger populations are needed.